Pembelajaran Membaca Permulaan pada Anak Tunagrahita Kategori Ringan - Novena Putri Devi (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This research is motivated by the importance of early reading learning in children from an early age, including mentally retarded children in the mild category. Mentally retarded children in the mild category are children who have intelligence disorders but cannot be separated from mentally retarded children in the severe category. With this intelligence disorder, early reading learning needs to be implemented properly so that children can take part in learning activities well too. The purpose of this study was to find out the learning process for beginning reading in mild mentally retarded children, as well as to find out the effectiveness of the learning methods used. Because mentally retarded children, of course, must be taught with techniques that suit their circumstances. This type of research is descriptive descriptive research using the literature study method. Literature study is used because it is in accordance with the objectives of previous research. The results showed that from the results of the analysis of selected literary studies, it was known that there were several methods/techniques that could be used in learning to read beginning in mild mentally retarded children. First, learning by using picture word cards. Based on the research results, this technique is very helpful in sharpening children’s memory, so that this technique is declared effective in learning to read beginning in mentally retarded children in the mild category. Second, the Mingel technique is by utilizing children’s social interaction accompanied by games. The results of the study show that this technique is also effective in improving children’s early reading skills. This technique can bring the enthusiasm of children in learning so that it makes it easier for children to accept the learning given.